KONSELOR PASTORAL SEBAGAI SAHABAT PEMUDA DI ERA DIGITAL - Pakpahan, Chichi; Sitorus, Christin; Siburian , Pebi; Silitonga, Derselli P. (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2025)
Adolescence is a pivotal period in individual development, where adolescents experience significant changes in physical, mental, social and emotional aspects. One of the main challenges faced is the management of strong emotions, which is often influenced by their interactions on social media. In the digital world, many teens choose to express their feelings through online platforms, which often only results in superficial interactions and does not solve their emotional problems in depth. Excessive use of social media can actually exacerbate feelings of loneliness and anxiety, and worsen social isolation. Therefore, the role of the pastoral counselor as a friend who is present in person becomes very important. With a love and empathy-based approach, pastoral counselors not only listen to the confessions, but also provide deeper emotional support and spiritual guidance that help teens find balance in their lives. Pastoral counselors can be a safe space for teens to talk about their feelings, address anxieties, and understand life challenges from a broader perspective, away from the negative impact of social media. This approach helps teens build healthier relationships, both emotionally and spiritually, and leads them to face life more readily without depending on social media.